Wojewódzkie fundusze ochrony środowiska i gospodarki wodnej jako podmioty udzielające pomocy publicznej przedsiębiorcom - Bartniczak, Bartosz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The Act on Conditions for Approving and Supervising Public Support for Entrepreneurs is in force in Poland since the year 2000. One of the areas addressed by state aid is environment protection. And one of the main entities that can provide state aid in this area is Regional Fund for Environmental Protection and Water Management. The aim of this article is to present the role of regional fund in this area, and to make analysis of given state aid. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 32-45